Core outcome set for the management of acute exacerbations of chronic obstructive pulmonary disease: the COS-AECOPD ERS Task Force study protocol. Issue 3 (14th September 2020) - Mathioudakis, Alexander G.; Abroug, Fekri; Agusti, Alvar; Bakke, Per; Bartziokas, Konstantinos; Beghe, Bianca; Bikov, Andras; Bradbury, Thomas; Brusselle, Guy; Cadus, Cordula; Coleman, Courtney; Contoli, Marco; et al.
Randomised controlled trials (RCTs) on the management of COPD exacerbations evaluate heterogeneous outcomes, often omitting those that are clinically important and patient relevant. This limits their usability and comparability. A core outcome set (COS) is a consensus-based minimum set of clinically important outcomes that should be evaluated in all RCTs in specific areas of health care. We present the study protocol of the COS-AECOPD ERS Task Force, aiming to develop a COS for COPD exacerbation management, that could remedy these limitations. For the development of this COS we follow standard methodology recommended by the COMET initiative. A comprehensive list of outcomes is assembled through a methodological systematic review of the outcomes reported in relevant RCTs. Qualitative research with patients with COPD will also be conducted, aiming to identify additional outcomes that may be important to patients, but are not currently addressed in clinical research studies. Prioritisation of the core outcomes will be facilitated through an extensive, multi-stakeholder Delphi survey with a global reach. Selection will be finalised in an international, multi-stakeholder meeting. For every core outcome, we will recommend a specific measurement instrument and standardised time points for evaluation. Selection of instruments will be based on evidence-informed consensus. Our work will improve the quality, usability and comparability of future RCTs on the management of COPD exacerbations and, ultimately, the care of patients with COPD. Multi-stakeholder engagement and societal support by the European Respiratory Society will raise awareness and promote implementation of the COS. The COS-AECOPD @EuroRespSoc Task Force is developing a core outcome set (COS) for #COPD exacerbation management. COS is an agreed minimum set of clinically important outcomes to be evaluated in all RCTs and can improve their usability and comparability. https://bit.ly/3ftAXk6